2012
DOI: 10.1073/pnas.1207170109
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitors of Smoothened ciliary localization and ciliogenesis

Abstract: Vertebrate Hedgehog (Hh) signals involved in development and some forms of cancer, such as basal cell carcinoma, are transduced by the primary cilium, a microtubular projection found on many cells. A critical step in vertebrate Hh signal transduction is the regulated movement of Smoothened (Smo), a seven-transmembrane protein, to the primary cilium. To identify small molecules that interfere with either the ciliary localization of Smo or ciliogenesis, we undertook a high-throughput, microscopy-based screen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…The inhibitory effect of microtubule inhibitors on Hh signaling has been demonstrated by unbiased screens that have identified such agents indirectly, as inhibitors of GLI activity, or by direct inhibition of cilia formation and function (33,56,57). Thus far, the anti-microtubule agents identified in these screens are either highly toxic, or at early stages of characterization.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of microtubule inhibitors on Hh signaling has been demonstrated by unbiased screens that have identified such agents indirectly, as inhibitors of GLI activity, or by direct inhibition of cilia formation and function (33,56,57). Thus far, the anti-microtubule agents identified in these screens are either highly toxic, or at early stages of characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Heralding such a possibility, a recent study identified small molecules that selectively affect smoothened (a Hedgehog signalling protein) cilia-related trafficking, and these could thus be employed as anti-tumour compounds 131 .…”
Section: A Complex Ciliary Trafficking Pathway Only Starting To Yieldmentioning
confidence: 99%
“…Hedgehog’s oncogenic activity has galvanized small molecule discovery efforts, resulting in the recent approval of vismodegib (Erivedge) for the treatment of advanced basal cell carcinoma [5]. Vismodegib, like several other Hh inhibitors under clinical study, interferes with transduction of the Hh signal by antagonizing a cell surface receptor called Smoothened [6, 7]. While a major milestone, alternative approaches to combat aberrant Hh activity are worth pursuing for combination therapy and to contend with clinical resistance to vismodegib [8-10].…”
mentioning
confidence: 99%